1998
DOI: 10.1093/ajcn/68.6.1196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a stearic acid-rich, structured triacylglycerol on plasma lipid concentrations

Abstract: Background: Structured lipids are being incorporated into foods to reduce their energy value. One such lipid is rich in stearic acid. Objective: The objective of this study was to compare the effects on plasma lipids of a stearic acid-rich triacylglycerol and a fat rich in palmitic acid in hypercholesterolemic subjects. Design: Fifteen subjects with an average plasma cholesterol concentration of 6.13 ± 0.80 mmol/L initially ate a low-fat diet for 2 wk (run-in period), followed in random order and blinded fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Although animal studies (17,18) and studies in newborns (13) have shown effects of the sn-configuration of fatty acids, this effect could not be confirmed in human studies (14). Zock et al (10) concluded that a large difference in fatty acid configurations (eg, sn position) had little effect on blood lipid and lipoprotein concentrations, which is supported by others (19,20). No significant differences in the total:HDL cholesterol ratio, which is suggested to be a predictor of CVD development rather than LDL per se (21), were found after intake of the different test 2 All values are means 6 SDs.…”
Section: Discussionmentioning
confidence: 99%
“…Although animal studies (17,18) and studies in newborns (13) have shown effects of the sn-configuration of fatty acids, this effect could not be confirmed in human studies (14). Zock et al (10) concluded that a large difference in fatty acid configurations (eg, sn position) had little effect on blood lipid and lipoprotein concentrations, which is supported by others (19,20). No significant differences in the total:HDL cholesterol ratio, which is suggested to be a predictor of CVD development rather than LDL per se (21), were found after intake of the different test 2 All values are means 6 SDs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies comparing C16:0 with C18:0 demonstrated similar effects on the lipid profile. Nestel et al (1998) compared the effects on plasma lipids of a C18:0‐rich diet versus C16:0 in hypercholesterolemic subjects and demonstrated that plasma TC concentrations with the low‐fat, C18:0‐rich, and the C16:0‐rich diets were not significantly different but lower than those measured during the habitual diet period. Neither HDL‐C nor plasma TAG differed significantly among the three study diets.…”
Section: Effects Of Palm Oil and Its Fractions On Blood Lipids And LImentioning
confidence: 99%
“…Salatrim™ had no effect on blood lipids and lipoprotein metabolism, but Caprenin™ was shown to be hypercholesterolemic in men [113,116,117]. The hypercholesterolemic effect of Caprenin™ was discussed previously.…”
Section: Introductionmentioning
confidence: 99%